2020
DOI: 10.1002/app.49865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hollow glass beads on density and mechanical properties of silicone rubber composites

Abstract: In this work, low density hollow glass beads (HGB)/silicon rubber (SR) composites were prepared by solution method and flocculation process. The prepared samples were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, tensile test, and friction test. The results show that the densities of SR composites decrease from 1.140 to 0.792 g/cm3 with the addition of HGB. By comparing theoretical density with true density, it can be estimated that the ratio of shattered HGB increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thus, the interfacial compatibility between HGM and PIF was effectively improved to enhance the performance in PIF. 27,28 It is worth noting that the mechanical properties of the composite foams decrease with the further increase of M-HGM content. However, it is still higher than that of pure PIF and can resist the compression weight of 100 g without deformation.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Thus, the interfacial compatibility between HGM and PIF was effectively improved to enhance the performance in PIF. 27,28 It is worth noting that the mechanical properties of the composite foams decrease with the further increase of M-HGM content. However, it is still higher than that of pure PIF and can resist the compression weight of 100 g without deformation.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Graphene improved the physical and chemical bonding of the interface in the material and can thus improve the mechanical properties of the composites. Quan et al 15 modified hollow microspheres with a silane coupling agent, and the tensile strength of the composite was increased by 28.2% by enhancing interfacial chemical bonding. Wu et al 16 modified hollow microspheres with carbon nanotubes to improve the physical bonding at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also revealed that the combination of mica powder (MP) with other fillers improved the mechanical properties of composites under tensile and tearing modes, such as MP/wollastonite-filled styrene-butadiene rubber (SBR)/natural rubber (NR) [12] and MP/graphite flakes-filled ethylene propylene diene monomer (EPDM) [13]. In addition, due to the unique structure of hard glass on the outside and inert gas on the inside, hollow glass beads (HGB) are also widely used to fabricate polymer composites for mechanical reinforcement in different applications, such as nitrile and silicone rubbers [14,15].…”
Section: Introductionmentioning
confidence: 99%